Analisis Putusan Nomor 66/Pid.B/2014/Pn.Amp dalam Kasus Pidana Pembunuhan: Adanya Pertimbangan Hakim yang Tidak Sesuai dengan Ketentuan Hukum - Gunawan Widjaja; Delia Bazlina (Bulletin of Community Engagement, 2024)
This study analyzes Decision Number 66/Pid.B/2014/PN.Amp in a murder case, highlighting the alleged inconsistencies in judicial considerations with legal provisions. A normative approach was used to evaluate the consistency of the judge's considerations with the available evidence, adherence to legal procedures, and principles of justice. The analysis reveals that the District Court of Amlapura applied Article 338 of the Criminal Code (ordinary murder), despite evidence suggesting premeditation that should be categorized under Article 340 (premeditated murder). The High Court of Denpasar corrected this by applying Article 340 and increasing the prison sentence to 13 years. This correction aligns better with the facts and principles of justice, setting a better legal precedent for judicial practices in Indonesia.